Circular migration and multilocational livelihood strategies in rural India - Deshingkar, Priya (ed.); Farrington, John (ed.) (New Delhi, 2009)
Circular migration has become the enduring mobility pattern of the poor in agriculturally marginal areas of India. This volume deals with millions of unskilled and semiskilled poor who migrate away from the rural region in search of jobs that are mostly in the informal organized sector. It studies migration using different conceptual frameworks intended to provide coherence across the studies in order to draw out policy conclusions. With case studies pulled together from some of the poorest and most deprived parts of India, this volume shows how important migration has become in sustaining and improving rural livelihoods.
Keywords: Migration-Rural areas-India